Case Report: Epstein-Barr virus negative lymphoepithelioma-like cholangiocarcinoma: a rare tumor that deserves further exploration. Report of a case with distinct genomic and clinical features - Corallo, Salvatore; Milani, Chiara; Vanoli, Alessandro; Gallotti, Anna; Pagani, Anna; Serra, Francesco; Maestri, Marcello; Ravetta, Valentina; Lasagna, Angioletta; Pedrazzoli, Paolo; Agustoni, Francesco (Frontiers in Oncology, 2025)
Lymphoepithelioma-like cholangiocarcinoma (LEL-CC) is a rare variant of cholangiocarcinoma characterized by undifferentiated malignant epithelial cells and a significant lymphoid infiltrate. Due to its rarity, there is currently no established treatment protocol for LEL-CC, and limited data are available regarding the genomic landscape of this rare tumor. In this report, we present the case of an 84-year-old woman with a history of Hepatitis C-related cirrhosis who was diagnosed with EBV-negative LEL-CC. This tumor presented as a double primary tumor together with a moderately differentiated hepatocellular carcinoma, at the time of first diagnosis. After surgical resection, the patient experienced a relapse with intracolonic metastasis. Comprehensive genomic profiling revealed unique genetic features consistent with LEL carcinoma of other sites of origin. The genetic and clinical characteristics of our case highlight the need for further research on this rare variant of cholangiocarcinoma. Gaining insights into the molecular mechanisms behind this type of cancer could lead to the development of effective targeted therapies or immunotherapeutic approaches.